Cephalic hedgehog expression is regulated directly by Sox17 in endoderm development of Xenopus laevis - Yagi, Yumihiko (Springer Netherlands, 2008)
In early development of animals, hedgehog (Hh) genes function as morphogen in the axis determination and the organ formation. In Xenopus, three hedgehog genes, sonic (shh), banded (bhh), and cephalic (chh), were identified and might organize various tissues and organs in embryogenesis. Here, we report the spatial and temporal regulation of Xchh which is expressed in endoderm cells differentiating to digestive organs. Xchh expression in endoderm was inhibited by ectopic expression of the dominant-negative activin receptor, tAR. Moreover, a maternally inherited transcription factor VegT and its downstream regulators activated Xchh expression. These indicates that Xchh is regulated by the factor involved in the cascade originated from VegT via activin/nodal signals. Using the Sox17α-VP16-GR construct, we showed that Xchh expression might be induced directly by transcription factor Sox17.